Influence of Rationalization on Occurrence of Occupational Fraud Loss in Public Secondary Schools in Nairobi County, Kenya - Limo, Silas; Gathoni, Benson; Kimungunyi, Sammy (International Journal of Modern Risk Management, 2025)
Purpose: The purpose of this study was to determine the influence of rationalization on occurrence of occupational fraud loss in public secondary schools in Nairobi County, Kenya. Methodology: The study adopted a positive paradigm with a descriptive design which targeted a sample of 101 public secondary schools in Nairobi County. An audit team leader from the government was the respondent for each school. Fishers sampling formulae was used to get a sample of 96 respondents. Stratified random sampling was used to ensure that all sub-counties were fairly represented in the sample. Primary data was used in this study through the administration of a semi structured questionnaire, data collected was analyzed using the statistical package for social sciences software (SPSS) version 21, using the linear regression analysis. This study adopted a positive paradigm and the results collected were presented in form of descriptive statistics, that is, mean and standard deviation in tables, charts and figures. Findings: The study found that occupational fraud loss in public secondary schools is significantly influenced by rationalization (β = 0.343; p<0.05). Unique Contribution to Theory, Practice and Policy: From a policy perspective, the study highlights the importance of implementing stringent internal control mechanisms in educational institutions. Policymakers should prioritize frameworks that enhance fraud detection and prevention, including mandatory financial audits, job rotation, and whistleblowing policies to deter fraudulent activities.